PS05 Men With Prostate Cancer Make Positive Dietary Changes Following Treatment in a Randomised Trial: A Prospective Cohort Study. (17th September 2012) - Avery, KNL; Donovan, JL; Gilbert, R; Davis, M; Emmett, P; Down, E; Oliver, S; Neal, DE; Hamdy, FC; Lane, JA
Abstract : Background: Prostate cancer (PC) is the second most frequently diagnosed cancer of men worldwide. A healthy diet may improve clinical outcomes but there is currently no disease-specific dietary advice available to aid survivorship after a PC diagnosis. The effect of a PC diagnosis on men's diet remains uncertain because, although cancer survivors report dietary changes, the direction and magnitude of changes are poorly understood. This study examined dietary changes in men before and after treatment for PC within the Prostate Testing for Cancer and Treatment (ProtecT) randomised trial. Methods: This was a prospective cohort study embedded within the ProtecT randomised trial of treatments for PC. Participants were men aged 50–69 years tested for PC in primary care centres in nine areas of the UK. 3935 men completed a validated food frequency questionnaire before diagnosis and 678 with localised disease repeated the questionnaire one year later (response 82.7%). Pre-diagnosis dietary intakes of men with different diagnoses subsequently (negative diagnosis, at risk, localised PC, advanced PC) were compared using linear regression. Dietary changes after a diagnosis of localised PC were examined using non-parametric tests. Effects of cancer treatments (radical prostatectomy, conformal external beam radiotherapy or active monitoring) were examined using linear regression. Results: Before diagnosis, all men consumed largely similar amounts of key nutrients and foods. The diagnosis of localised PC led to dietary changes in 29.2% of men. Changes observed were generally in a healthy direction, with 234 (34.7%) men eating more fresh tomatoes (p<0.0001) and 156 (23.5%) more tomato products (p=0.01). 271 (40.0%) men consumed more protein (p<0.0001) and 193 (28.6%) more fruit/vegetable juice (p<0.0001). Less macronutrients were obtained from dairy products (p<0.01). Men undergoing active monitoring (regular assessment of disease status) drank more fruit/vegetable juice than men who had received surgery (p=0.004). Conclusion: Diagnosis of localised PC prompted around one third of men to adopt healthier diets and eat more 'prostate-healthy' foods. Dietary choices were influenced by treatment received, with more interest in dietary factors for survivorship in men undergoing active monitoring than those undergoing radical treatment. PC survivors are motivated to improve their diet and are able to access and act on healthy eating advice. Diagnosis of PC may serve as a "teachable moment", thereby providing opportunities for clinicians to provide targeted advice that could be beneficial to general (and prostate-specific) health and to support survivorship.